1999
DOI: 10.1021/ma9905627
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Salt Effects on DNA Conformation:  Experiment and Theory

Abstract: The condensation of a single DNA can be induced by multivalent counterions and is thought to be due to ion−ion correlations. Both Monte Carlo simulations and fluorescence microscopy experiments confirm this picture. The effect is less pronounced for chain counterions (polyamines) than for simple spherical counterions with the same charge. When simple salt is added to the system, the polyelectrolyte unfolds. MC simulations show that this is due to a competition between the different small ion species. The multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…6 that compaction of the polyanion occurs when the polycations are closer to the negative chain and thus thermodynamically restrained in their motion. This can be the explanation for the fact that large amounts of spermidine and spermine are necessary to induce the compaction of DNA in single molecule experiments [50,51].…”
Section: Effect Of the Chain Lengthmentioning
confidence: 98%
See 2 more Smart Citations
“…6 that compaction of the polyanion occurs when the polycations are closer to the negative chain and thus thermodynamically restrained in their motion. This can be the explanation for the fact that large amounts of spermidine and spermine are necessary to induce the compaction of DNA in single molecule experiments [50,51].…”
Section: Effect Of the Chain Lengthmentioning
confidence: 98%
“…It was observed that in the presence of polyamines DNA undergoes a discrete conformational change from coil to globule and that, even with spermine, having four charges per molecule, an excess of positive charges was required for the compaction to initiate. Furthermore, the concentrations of the polycations required to induce compaction of DNA decrease substantially with the increase of the charges in the chain, differing by about one order of magnitude [50,51]. When longer polycations were used, charge neutralization was not even required [49].…”
Section: A Dynamic Light Scattering Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This can again be discussed in terms of the attractive electrostatic interactions and the large size of surfactant aggregates formed. However, the latter effect is apparently not required since in studies of DNA compaction induced by other co-solutes, organic solvents, electrolytes, etc., a coexistence of coils and globules is also found (25,34). Essentially all of these studies have concerned vesicles which are not thermodynamically stable.…”
Section: Dna Is Compacted By Cationic Surfactantsmentioning
confidence: 99%
“…Here the assumption of uncorrelated positions of the counterions does not hold any longer. The role of counterion correlations as charge density and counterion valency increase is best illustrated by an example from recent calculations by Khan et al (24,25), an example with direct relevance for DNA. Figure 5 shows the end-to-end distance for a polymer as it is progressively charged up.…”
Section: Attractive Ion-ion Correlation Effects For Dna In the Presenmentioning
confidence: 99%